City of Malacca / The Sultanate of Malacca and its Role in the Islamization of the Malay Peninsula - AYDINLI, OSMAN (SAKARYA UNIV, 2021)
Malacca which was founded by Parameswara at the end of the 14th century or the start of the 15th is situated on the west coast of the Malay Peninsula. The Malacca Sultanate, which was established in Malaka and reigned for more than a century, is recognized as one of the Malay Peninsula's most significant states. Malacca's emergence as an international trading center has played a significant role in the spreading of Islam through the Malay Peninsula and the surrounding states. Malacca has successfully attracted traders and scholars from foreign countries who came to run business and teaching Islam. Despite traders and scholars, Malacca's rulers play an important role in the development of Islam in Malacca and the Malay Peninsula through the economy and political strategy. The advent of Islam has influenced Malacca society and Malay Peninsula's states in administration, religious practice, socio-culture, and traditions. Malacca which was inhabited by non-Muslim society shows the impact of Islamic law in the state's main laws which were Undang-Undang Melaka (Malacca Law) and Undang-Undang Laut Melaka (Malacca Maritime Code) after the arrival of Islam. Islamic teaching was actively carried out in Malacca. Sultan would send a messenger to other Sultan in the other Malay states to ask about religious issues. This tradition has been one of the main reasons for the development of Islam in Malacca and the Malay Peninsula. Thus, this article will discuss the arrival and development of Islam in the Malay Peninsula during the Malacca Sultanate era and the impact it has on the states and their society.
Keywords: Malay Peninsula; Malacca city; Malacca Sultanate; Islamization; Islamic Culture